THE FUNKTION OF INFORMATION AND COMMUNICATION TECHNOLOGY IN THE QUALITY OF TEACHING SYSTEM - BLAŠKO, Michal (Trends in education, 2010)
Report is concerned with influence of using of ICT means and their importance for quality of teaching management. It brings results of surveys in which teachers have reviewed the importance of indicators in areas of quality of teaching, including the indicator of using of ICT in teaching.
Keywords: using information and communication technology; teacher´s professionalism; quality of teaching system; areas and indicators of quality of teaching